The Role of Islamic Religious Education: The Key to Forming a Generation With Morals and Knowledge - Muslimin, Muslimin (Al-Ilmu, 2025)
Islamic Religious Education (PAI) has a fundamental role in shaping a moral and knowledgeable generation. This study aims to analyze the role of PAI in shaping the character and intellectual insight of the younger generation by using the Systematic Literature Review (SLR) method. The SLR method is a systematic approach used to identify, select, and analyze previous research in order to gain a deeper understanding of a topic. The main stages in this method include literature identification, source selection, data analysis, and interpretation of results. The results showed that PAI is a conscious and planned effort in guiding students to understand, appreciate, and practice Islamic teachings in daily life. The concept of PAI includes aspects of faith, worship, morals, and muamalah based on the Qur'an and Hadith. Learning methods in PAI include lectures, discussions, exemplification, and direct practice in performing worship and Islamic behavior. Moral education in Islam must be instilled early through the role of family, school, and society